Can someone help with this
![Can someone help with this class=](https://us-static.z-dn.net/files/da7/3c7a019c5b93671e73a750762e83c0f2.png)
Hi there!
A.
We can use the work-energy theorem to solve.
Initially, both blocks have gravitational potential energy, which is then converted to kinetic energy.
Recall:
[tex]U = mgh \\[/tex]
U = Potential Energy (J)
m = mass (kg)
g = acceleration due to gravity (m/s²)
h = height (m)
And at the end, block 2 has both kinetic and potential energy. Kinetic is defined as:
[tex]KE = \frac{1}{2}mv^2[/tex]
v = velocity (m/s)
We can do a summation of initial and final forces.
Initial:
[tex]E_i = m_2g\frac{h}{2} + m_1gh[/tex]
Final:
[tex]E_f = \frac{1}{2}m_2 v^2 + m_2g\frac{3h}{2} + \frac{1}{2}m_1 v^2[/tex]
Set the two equal (no energy loss in this situation) and solve for velocity.
[tex]m_2g\frac{h}{2} + m_1gh = \frac{1}{2}m_2 v^2 + m_2g\frac{3h}{2} + \frac{1}{2}m_1 v^2\\\\m_2g\frac{h}{2} + m_1gh - m_2g\frac{3h}{2} = \frac{1}{2}m_2 v^2 + \frac{1}{2}m_1 v^2\\\\v^2 = \frac{gh(\frac{m_2}{2} + m_1 - \frac{3m_2}{2})}{\frac{1}{2}m_2 + \frac{1}{2}m_1}\\\\v = \sqrt{\frac{gh(\frac{m_2}{2} + m_1 - \frac{3m_2}{2})}{\frac{1}{2}m_2 + \frac{1}{2}m_1}}\\\\v = \boxed{3.704 \frac{m}{s}}[/tex]
**This can be solved in a simpler way using a summation of forces.
B.
Now, we can do a summation of forces to solve. First, we must solve for the acceleration of the system now that we have found the velocity. Use the kinematic equation:
[tex]v_f^2 = v_i^2 + 2ad[/tex]
Initial velocity is 0 m/s, so:
[tex]v_f^2 = 2ad\\\\a = \frac{v_f^2}{2d} = \frac{(3.704^2)}{2(2.10)} = 3.267 \frac{m}{s^2}[/tex]
Now, we can use a summation of forces for any block. We can do block 1:
[tex]\Sigma F = m_1g - T[/tex]
Using Newton's Second Law:
[tex]m_1a = m_1g - T\\\\T = m_1g - m_1a \\T = m_1 (g - a) = 4.10(9.8 - 3.267) = \boxed{26.828 N}[/tex]